2012
DOI: 10.1093/eurpub/cks073
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and subjective health among students reporting disability or chronic illness in 11 Western countries

Abstract: In all countries studied, students reporting D/CI were more likely to report being victims of bullying. Victims of bullying reported more negative subjective health outcomes regardless of their D/CI status. Although inclusive education is currently a major topic of educational policies in most countries, additional efforts should be made to improve the quality of the integration of students with D/CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 34 publications
9
49
0
2
Order By: Relevance
“…The review identified that while peer support is important for children with long term conditions, many of them experience loneliness, related to their condition, as a challenge. These review findings lend support to other international studies on disability/chronic illness which reported that children want to be seen as normal and the same as their peers, however, fear of rejection and the stigma associated with their condition often prevents them from disclosing their illness to peers and may prevent them from fully integrating in their peer group (Sentenac et al, 2013). Many children believe that visibility of their illness will lead to teasing and cause their peers to have negative perceptions of them relating to issues such as their inability to participate in the same activities and have the same amount of fun as them (King, MacDonald, & Chambers, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The review identified that while peer support is important for children with long term conditions, many of them experience loneliness, related to their condition, as a challenge. These review findings lend support to other international studies on disability/chronic illness which reported that children want to be seen as normal and the same as their peers, however, fear of rejection and the stigma associated with their condition often prevents them from disclosing their illness to peers and may prevent them from fully integrating in their peer group (Sentenac et al, 2013). Many children believe that visibility of their illness will lead to teasing and cause their peers to have negative perceptions of them relating to issues such as their inability to participate in the same activities and have the same amount of fun as them (King, MacDonald, & Chambers, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Many children believe that visibility of their illness will lead to teasing and cause their peers to have negative perceptions of them relating to issues such as their inability to participate in the same activities and have the same amount of fun as them (King, MacDonald, & Chambers, 2010). Sentenac et al (2013) found that children with long term conditions regularly experience peer victimisation at school. Children with long term conditions often underreport their symptoms in an effort to present themselves as healthy and as such, having a long term condition impacts on both the physical and social functioning of affected children through peer separation resulting from school absences and hospital stays (Pinquart & Shen, 2011a;Pinquart & Teubert, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these (82%) were conducted in the USA (see Table 4). Five of these studies reported aspects of adaptation such as forward-back translations, content validity, item completeness, and cultural appropriateness but without reporting any psychometric data [44, 4750]. Among those that reported psychometric data, only 6 studies [9, 18, 5154] reported this data for an entire HRB tool or entire tool from which HRB items were borrowed while the rest reported only data for select items from the HRB tool.…”
Section: Resultsmentioning
confidence: 99%
“…Our results also indicate that violence related behaviors are frequently investigated among chronically ill adolescents. Adolescents with chronic illnesses often fall victim of violence such as bullying, assault and forced sexual encounters [17, 50]; and thus raising the need for increased research on this matter. On the other hand, our findings show that poor hygiene, inadequate sleep and behavior resulting to unintentional injury were the least frequently assessed forms of HRB in this review.…”
Section: Discussionmentioning
confidence: 99%
“…People with long term conditions and disabilities were frequently victimised due to being "different" from others in cases of visible impairments (Horowitz et al, 2004), or because of adopting a lifestyle that differs from peers (Sentenac et al, 2011). The impact of offline victimisation on disabled people includes mental health consequences (Hugh-Jones & Smith, 1999;Sheridan & Grant, 2007), physical health complaints (Sentenac et al, 2013;Zinner, Conelea, Glew, Woods, & Budman, 2012) and disruption in managing the health condition (Sentenac et al, 2011). On top of the documented discrimination against people with disabilities in offline context, electronic communications had extended physical environments to virtual ones, eliminated international borders and provided harassers with anonymity (Sheridan & Grant, 2007), which lead to "cyber-victimisation" incidents.…”
Section: Introductionmentioning
confidence: 99%